Cardioprotective Roles of Endothelial Progenitor Cell-Derived Exosomes - Zeng, Cai-Yu; Xu, Jia; Liu, Xin; Lu, Yuan-Qiang (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases (CVDs) are still leading killers of human health and reduced quality of life, and are also gaining in prevalence worldwide. Endothelial progenitor cells (EPCs) transplantation holds great promise due to potential of vasculogenesis, angiogenesis and protective cytokine release, which present an important mechanism of EPCs therapy for CVDs. In reality, many investigations attributed the therapeutic effects of EPCs transplantation to its secreting paracrine factors rather than differentiation function. Of note, the previous studies suggested that EPCs could also release exosomes (diameter range 30-150nm), which carried various of lipids, proteins and abundantly microRNAs. The EPC-derived exosomes (EPC-EXs) acted on hearts and vessels, and then exerted anti-inflammation, anti-apotosis, inhibition of endothelial-to-mesenchymal transition（EndMT）and cardiac fibrosis, and anti-vascular remodeling , which were considered as protective effects for CVDs. In this article we summarize the functional relevance of using EPC-EXs as therapeutically agents and detail the identified mechanisms that they use to exert their effects to promote prognosis of CVDs.